2017
DOI: 10.1186/s40478-017-0457-1
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic amyloidogenic elements in mutant NEFH causing Charcot-Marie-Tooth 2 trigger aggresome formation and neuronal death

Abstract: Neurofilament heavy chain (NEFH) gene was recently identified to cause autosomal dominant axonal Charcot-Marie-Tooth disease (CMT2cc). However, the clinical spectrum of this condition and the physio-pathological pathway remain to be delineated. We report 12 patients from two French families with axonal dominantly inherited form of CMT caused by two new mutations in the NEFH gene. A remarkable feature was the early involvement of proximal muscles of the lower limbs associated with pyramidal signs in some patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 32 publications
4
36
0
Order By: Relevance
“…In addition, the deep tendon reflex was absent in both upper and lower limbs. The phenotype was consistent with that shown in a previous study in which patients who carried another mutation of NEFH had muscle weakness in the proximal muscle of the lower and distal muscle of the upper limbs in the late stage of CMT2CC [10]. The data revealed that the phenotype of CMT2CC in a Chinese population appeared identical to that in a western population.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…In addition, the deep tendon reflex was absent in both upper and lower limbs. The phenotype was consistent with that shown in a previous study in which patients who carried another mutation of NEFH had muscle weakness in the proximal muscle of the lower and distal muscle of the upper limbs in the late stage of CMT2CC [10]. The data revealed that the phenotype of CMT2CC in a Chinese population appeared identical to that in a western population.…”
Section: Resultssupporting
confidence: 80%
“…2). Thus, the expression of mutant NEFH led to aggregation of NEFH protein as in a previous report of mutant NF proteins leading to similar aberrant aggregation [10-12]. …”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Our study, therefore, is also the first to confirm the general concept of CAE, and to corroborate its pathogenic relevance. Strikingly, the disease associated with the unmasking of CAEs in both genes is CMT2 (Hoyer et al., ; Jacquier et al., ; Rebelo et al., ; present study). This suggests that susceptibility to CAE‐mediated aggregation is particularly high in peripheral axons.…”
mentioning
confidence: 48%
“…A somewhat related phenomenon, however, has been reported very recently. Two studies investigated distinct frameshift variants in the NEFH gene (Jacquier et al., ; Rebelo et al., ). These variants all localized to the terminal exon and are thus immune to NMD.…”
mentioning
confidence: 99%